Dampak Pembangunan Jalan Tol Trans Pekanbaru-Bangkinang terhadap Penjual Makanan Tradisional Lopek Bugi Danau Bingkuang - Ruli Hamsana; Resdati Resdati (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
The construction of toll roads is a national government development project aimed at connecting various regions with faster and easier transportation routes. The construction of toll roads brings various impacts on the surrounding environment, both positive and negative, especially in the areas they pass through. Toll road development is one of the essential infrastructures designed to improve connectivity and transportation efficiency between regions. However, the impact of toll road construction on traders, both small and large, often becomes a significant concern. This study aims to analyze the impact of toll road construction on "Lopek Bugi" traders, particularly those operating around the Lake Bingkuang area, Tambang District, Kampar Regency. The research method used is a descriptive quantitative approach. The sampling technique used is census sampling, where the entire population is considered as the sample. In this study, data processing and analysis are conducted using frequency tests with SPSS. Based on field research and data analysis, it was found that toll road construction has varied impacts. On one hand, better accessibility can increase market potential for traders located in areas farther from the city center. On the other hand, traders directly affected by toll road construction often experience a decline in income due to the loss of customers, disruptions in traffic flow, or even the closure of their stalls.